Метод підвищення чутливості при швидкісній комплексній аналоговій і комп'ютерній обробці інформаційних сигналів в приладах ультразвукового контролю - Плєснецов, Сергій Юрійович; Мигущенко, Руслан Павлович; Сучков, Григорій Михайлович (Донецький національний технічний університет, 2017)
Запропоновано метод підвищення чутливості систем неруйнівного контролю при обробці даних, заснований на методі прямого перетворення високочастотних сигналів. Виконано математичне рішення задачі з обробки вхідного сигналу з метою фільтрування та підсилення. Встановлено, що за запропонованою технологією сигнали завад і шумів з частотами, що відрізняються від робочої частоти, залежать від різниці між робочою частотою та відокремленими частотами завад і можуть бути відфільтровані. Розроблено схему пристрою для швидкої обробки прийнятих ультразвукових імпульсів відбитих з об’єкту контролю для випадку використання хвиль Релея. Метод реалізований в приладі.

Предложен метод повышения чувствительности систем неразрушающего контроля при обработке данных, основанный на методе прямого преобразования высокочастотных сигналов. Выполнено математическое решение задачи по обработке входного сигнала с целью фильтрации и усиления. Установлено, что по предложенной технологии сигналы помехи шумов с частотами, отличающиеся от рабочей частоты, зависят от разницы между рабочей частотой и отдельными частотами помех и могут быть отфильтрованы. Разработана схема устройства для быстрой обработки принятых ультразвуковых импульсов отраженных с объекта контроля для случая использования волн Рэлея. Метод реализован в приборе.

A method for increasing the sensitivity of nondestructive testing systems in data processing based on the method of direct high-speed high-frequency signals conversion is proposed. A mathematical solution of the problem of processing the input signal for the purpose of filtering and amplification is performed. Said soultion is based on modified Reyleigh wave equation analysis. Combined methods of data analysis were used. It is found, that usage of analog sybsystems can greatly increase processing speed for complex calculations. The solution has been split for corresponding blocks for each sybtype of waves and noises involved. The echo wave signal from potential defect has been separated from the rest equations. It is also found that, according to the proposed technology, signals of noise and noise with frequencies that differ from the operating frequency depend on the difference between the operating frequency and the individual interference frequencies and can be filtered out. Filtering algorithm is proposed. A scheme of the device for fast processing of received ultrasonic pulses reflected from the object of control for the case of using Rayleigh waves is developed. The device proposed includes electronic computing means, generator of probing pulses, electroacoustic transducer, four multipliers and filters, adder, testing results recorder. A signal in the scheme given is supposed to be subsequently processed via filters and multipliers in order to reach easily readable and understandable waveform to be displayed for the end user. A specialized computerized defectoscope for electromagnetic and acoustic high-speed testing with filtering algorithm based software solution is created. The device has been tested in lab environment and has shown proper results. The system developed uses Windows PC based platform with additional schemes for signal input and processing. The software part has been developed via C++ programming language and can be built for multiple operating systems
Метод повышения чувствительности при скоростной комплексной аналоговой и компьютерной обработке информационных сигналов в приборах ультразвукового контроля
The method of sensitivity increase for high-speed complex analog and computer processing of information signals in ultrasonic devices
Keywords: неруйнівний контроль; акустичний контроль; алгоритм обробки; підсилення сигналу; фільтрація завад; неразрушающий контроль; акустический контроль; алгоритм обработки; усиления сигнала; фильтрация помех; nondestructive testing; acoustic control; processing algorithm; signal amplification; interference filtering